Development Strategy of Msmes With The Pentahelix Model (A Study on MSMEs in the Malang City) - Trianti, Khoiriyah; Kurniati, Rini Rahayu; Widayawati, Eny; Aini, Yulis Nurul (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research examines the development strategy of MSMEs in Malang City, Indonesia, during the Covid-19 pandemic. The goals are to evaluate the impact of the Pentahelix model on MSMEs, create an analytical model highlighting the role of Pentahelix in enhancing MSME performance, and explore collaborative efforts of stakeholders in empowering the MSME sector. Quantitative research methods, including interviews, observations, and questionnaires, were used to gather data from MSME actors in Malang City. Descriptive analysis was employed to interpret the collected information. Interviews and observations with MSME actors and government representatives were conducted to understand the Pentahelix collaboration. The findings show the significant impact of the pandemic on MSMEs, leading to decreased sales. The Pentahelix model, involving collaboration among the government, private sector, community, academia, and media, is identified as a potential solution. The study highlights the roles of each stakeholder in empowering MSMEs, including government support programs, academic initiatives, business contributions, community networking, and strategic use of social media. In summary, enhancing MSME sales turnover requires collaboration among academics, government, business people, community, and social media. The Pentahelix collaboration empowers MSMEs, with each stakeholder playing a vital role. The research emphasizes the importance of a holistic strategy to improve MSME performance, supported by academics, government, and business sector. These collaborative efforts establish a sustainable business environment for MSMEs in Malang City.